Silicea Gastrointestinal Gel Improves Gastrointestinal Disorders: A Non-Controlled, Pilot Clinical Study - B. Uehleke; M. Ortiz; R. Stange (Gastroenterology Research and Practice)
Aim. To investigate efficacy and tolerability of Silicea Gastrointestinal Gel in patients with gastrointestinal disorders. Methods. Open, prospective pivotal phase IV study with oral Silicea Gastrointestinal Gel over 6 weeks. Symptom score was part 1 of the Nepean Dyspepsia Index: 15 questions addressing intensity, frequency and impact of upper abdominal symptoms. 10 lower abdominal symptoms were asked analogously. A responder showed reduction of score of >50%. Results. 62 of 90 patients were evaluated per protocol. Upper and lower abdomen sum scores decreased already in the first three weeks (P<0.001), which continued the following three weeks (P<0.01). Mean symptom score for upper abdomen decreased from 52.2±31.0 to 33.7±28.7 (or by 35.4%; responder rate 37%); for lower from 39.6±24.7 to 22.6±21.7 (by 42.9%; responder rate 46%). Subgroups with diarrhea, IBS and GERD presented highest responder rates. 6% of patients reported adverse reactions with probable or possible relationship to the test product. Conclusions. Silicea Gastrointestinal Gel seems suitable beyond infectious acute gastrointestinal disorders. Responses are relevant for chronic functional disorders, but it remains unclear, how much of that might be placebo-effect. Controlled studies are recommended in gastrointestinal syndromes like IBS or GERD.